Syria : the making and unmaking of a refuge state - Chatty, Dawn, 1947- (London : Hurst & Company, 2017)
'The dispossession and forced migration of nearly 50 per cent of Syria's population has produced the greatest refugee crisis since World War II. This new book places the current displacement within the context of the widespread migrations that have indelibly marked the region throughout the last 150 years. Syria itself has harboured millions from its neighbouring lands, and Syrian society has been shaped by these diasporas. Dawn Chatty explores how modern Syria came to be a refuge state, focusing first on the major forced migrations into Syria of Circassians, Armenians, Kurds, Palestinians, and Iraqis. Drawing heavily on individual narratives and stories of integration, adaptation, and compromise, she shows that a local cosmopolitanism came to be seen as intrinsic to Syrian society. She examines the current outflow of people from Syria to neighbouring states as individuals and families seek survival with dignity, arguing that though the future remains uncertain, the resilience and strength of Syrian society both displaced internally within Syria and externally across borders bodes well for successful return and reintegration.'--Back cover.
Includes bibliographical references : pages 257-268 and index.
Keywords: Refugees -- Syria -- History; Syria -- Emigration and immigration -- History